INTENSITAS SERANGAN HAMA ULAT API (Setothosea asigna) PADA TANAMAN KELAPA SAWIT (Elaeis guineensis. JACQ) DI KECAMATAN TEBO TENGAH KABUPATEN TEBO - Yuza Defitri; Yulistiati Nengsih; Harianto Saputra (Jurnal Media Pertanian, 2017)
AbstractThis research aims to know the intensity of pest attacks the fire (Setothosea asigna) who attacked oil palm plants in Central Districts Tebo Tebo. This research has been carried out in the village of Mangunjayo, the village of Enclosure and the village of Tebo Tengah Sub-district Pandak Gulf County Tebo for 1 month in September 2016. Research carried out using the method of survey in the oil palm plantation folk who have produced (TM) in the village of Mangunjayo, the village of Enclosure and the village of Tebo Tengah Sub-district Pandak Bay District with an area of Tebo area 1 – 2 ha. Sampling plants at each site is divided in 5 plot. Each plot was taken 5 sample plants. The observations in the field can be inferred that the intensity of the attacks the highest api pest found in Palm oil plantation in the village of Tebo Tengah Sub-district Pandak Gulf County Tebo i.e. amounting to 36%. The intensity of the attack the lowest api there is a pest on Palm oil plantation in the village of Tebo Regency Central Sub Enclosure Tebo i.e. by 8%. The difference in intensity of pest attacks also in influence by difference of height, temperature, and humidity.Keywords: intensity of pest attacks and fire AbstrakPenelitian ini bertujuan untuk mengetahui intensitas serangan hama ulat api (Setothosea asigna) yang menyerang tanaman kelapa sawit di Kecamatan Tebo Tengah Kabupaten Tebo. Penelitian ini telah dilaksanakan di Desa Kandang, Desa Mangunjayo dan Desa Teluk Pandak Kecamatan Tebo Tengah Kabupaten Tebo selama 1 bulan  pada bulan September 2016. Penelitian dilakukan dengan menggunakan metode survei di lahan perkebunan kelapa sawit rakyat yang telah menghasilkan (TM) di Desa Kandang, Desa Mangunjayo dan Desa Teluk Pandak Kecamatan Tebo Tengah Kabupaten Tebo dengan luas areal 1 – 2 ha. Pengambilan sampel tanaman pada setiap lokasi dibagi dalam 5 plot. Masing-masing plot diambil 5 sampel tanaman. Hasil pengamatan di lapangan dapat disimpulkan bahwa intensitas serangan hama ulat api tertinggi terdapat di Perkebunan Kelapa sawit di Desa Teluk Pandak Kecamatan Tebo Tengah Kabupaten Tebo yaitu sebesar 36%. Intensitas serangan hama ulat api terendah terdapat di Perkebunan Kelapa sawit di Desa Kandang Kecamatan Tebo Tengah Kabupaten Tebo yaitu sebesar 8%. Perbedaan Intensitas serangan hama juga di pengaruhi oleh perbedaan ketinggian tempat, suhu, dan kelembaban.Kata Kunci : intensitas serangan dan  hama ulat api